Flexible GO/Nb2CTx hybrid films for high-performance piezoresistive sensors. (5th August 2021) - Li, Zhemin; Yan, Surong; Yang, Hongpeng; Jiang, Jingjing; Wei, Guodong; Xu, Shuaikai
Abstract: High-performance flexible piezoresistive sensors have attracted more and more scientific attention due to their promising applications in robotics and portable electronic devices. However, most flexible piezoresistive sensors require a fine structure design at the nanoscale, which makes the manufacturing process very complex and expensive. Two-dimensional (2D) transition metal carbides named MXene have been regarded as an important candidate material for piezoresistive sensors due to their good conductivity, large interlayer spacing, and the inherent nature of 2D materials. The interlayer spacing between MXene nanosheets would be varied under an external pressure, resulting in the conductivity modulation. To improve the sensitivity of MXene-based piezoresistive sensors, the interlayer spacing of MXene-based films should be further tuned and optimized. In this contribution, flexible Nb2 CT x -based films were developed using a simple filtration method and evaluated for piezoresistive sensors. 2D GO nanosheets were introduced between the Nb2 CT x layers to tune the interlayer spacing to enhance piezoresistive performance. The fabricated flexible piezoresistive sensors based on GO/Nb2 CT x films possess high sensitivity up to 228 kPa −1 and rapid response time as fast as 101 ms. This study would promote the application of MXenes-based 2D nanomaterials in the field of piezoresistive sensors.